Results of clinical validation of a new method of brachial plexus trunk distraction after neuroraphy - A. A. Bogov (jr.); I. F. Akhtyamov; V. I. Danilov; I. G. Starostina; I. G. Khannanova; A. A. Bogov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2023)
The paper describes the results of clinical testing of an apparatus for dosed traction of brachial plexus trunks. It is shown that in the presence of a 5 cm diastasis, it is possible to connect the nerve fragments and perform neurorhaphy without tension by bringing the shoulder to the head and bring the shoulder to the physiological position two and a half months after the reconstructive surgery.